An analysis of the academic learning challenges faced by first year students in a Durban Private Higher Education Institution - Razack, Fathima (The IIE, 2020)
This study makes visible the experiences of students transitioning to higher education from high school and previously marginalised backgrounds in South Africa. The structure of South African higher education institutions is alleged to perpetuate epistemic deafness through clinging to the past and westernised curriculum. In line with decolonial perspectives, the research adopted the interpretivist paradigm to engage first-year students in sharing academic learning challenges they faced when they transitioned from high school to a higher education institution. Designed as a case study, data for this research was collected using qualitative methodologies to enable an experiential understanding of the challenges faced by students in the transition process. Results reveal that the students in their first year of studying at a higher education institution face several academic learning challenges some of which are necessitated by a lack of preparation and unmet expectations. The institution lacks recognition of students from marginalised contexts, and their limited potential to re-shape higher education is systematically limited at enrolment. Students who grew up in underserved communities find it difficult to quickly adapt to the current online learning styles and access the English language. The study recommends that for students to thrive, the institution has to meet the students at their point of need through carefully designed strategies that include but are not limited to group discussions, extra lessons, tutorials, and workshops on academic writing skills.
Keywords: Learning challenges; First-year students; Student experiences; Private higher education; Academic readiness